ANTIAGGREGANT ACTIVITY OF THE ETHANOLIC EXTRACTS OF Solanum tuberosum IN HUMAN PLATELETS - BUITRAGO R., Diana M.; RAMOS R., Gloria; RINCÓN V., Javier; GUERRERO P., Mario F. (Vitae, 2009)
The plant Solanum tuberosum is used in Colombian folk medicine for the treatment of hypertension. We evaluated the antiaggregant properties on human platelets of an ethanolic extract (96%) obtained from the skin of tubers of this species. Extracts from two varieties, sabanera and pastusa revealed in vitro dose-dependent (10–100 mg/mL) antiaggregant effects on platelets stimulated with adenosindiphosphate (ADP 10 μM), epinephrine (300 μM), collagen (10 μg/mL), and arachidonic acid (150 μg/mL). The IC50 values for the sabanera and pastusa varieties were, respectively, 1,8 μg/mL and 0,4 mg/mL, against ADP; 4,4 μg/mL and 0,1 mg/mL against epinephrine; 34,1 μg/mL and 1,3 mg/mL against collagen, and 12,3 μg/mL and < 0,1 μg/mL, against arachidonic acid, a key precursor in prostaglandin synthesis. Our findings suggest that S. tuberosum has a promising pharmacological profile since it combines the hypotensive effects, previously described, with the antiaggregant ones; therefore, it is potentially useful for the treatment of cardiovascular disorders such as hypertension and coronary artery disease.